Supporting UK Baptist clergy health, wellbeing, and self-care: intervention development and testing - Green, Jamie I. (2024)
Background: An examination of the current national and international literature regarding Christian clergy health and wellbeing indicates significant health deficits against comparative adult populations. To date, UK research is scant, with no published works concerning the holistic health, wellbeing, and self-care behaviours of Baptist church clergy. The potential influence of clergy within communities, known health disparities, and the lack of UK-specific research highlight an imperative for further investigation in this occupational group.